El uso del levamisole en las enfermedades respiratorias crónicas. - Razón, Roberto; Miranda, Olga; Chao, Felipe; Pademi, Teresita; Morales, Jorge; Sánchez, Leandro (Revista Cubana de Pediatría, 2024)
Efectividad del levamisole en diversas enfermedades respiratorias crónicas.